Paths of Salt and Artistis Interactions with Cacela Velha: Two Public Art Projects Sustained by an Integrated View of Place Through Participatory Design - Pinto, Paula (2016)
This paper addresses the concept of an integrated perspective of place through participatory design in public art, namely in the development of the artistic projects Paths of Salt and Artistic Interactions with Cacela Velha. It begins with the explanation of the guiding concepts of the research and methodologies, such as place, emphatic and participatory approaches, alluding to the active investigation; and finishes with a detailed description of both projects and the analysis of their results.